Rancang Bangun Visualisasi Informasi Aktivitas Data Giling Pada Pabrik Gula Kebon Agung Malang - Saputro, Arief Dwi; Nurcahyawati, Vivine; Wulandari, Sri Hariani (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
In order to support the self-sufficiency program, the Sugar Factory (PG) Kebon Agung Malang to develop, through a program known as Program Development PT Kebon Agung (PPKA) in order to improve the capacity target of sugarcane to 15,000 tons of cane per day by year-end target of 2.7 million tons. To support the program, the directors of PT Kebon Agung requires information that can determine the level of development and the process of what happens during the milling of the Kebon Agung sugar factory.Currently, Kebon Agung sugar factory has a website report daily grind milling plant in reporting the results, addressed to the directors of PT Kebon Agung in Surabaya. However, the website reports only report daily grind, so that the directors cannot determine the level of development of the realization of the rollers in one year. And therefore required a visualization of information that can see the level of progress of the rollers in one year and can be viewed each process in the milled report.The result of this research is a website of information visualization activities of milled-based dashboards that contain information on the results of ground in one year with the proposed revitalization of the factory in the website, so that the directors who were in Surabaya, can determine the level of progress of milled sugar factories located in Malang in one year and can make proposals for the revitalization of the factory..Keywords: Milled Reports, Website, Information Visualization, Dashboard.